STUDY REGARDING THE TECHNOLOGIES FOR COMPLETE DENTURES REALIZATION - Monica Tatarciuc; Ionuţ Luchian; Anca Vițalariu; Ioana Mârţu; Diana Diaconu-Popa (Romanian Society of Oral Rehabilitation, 2021)
The materials frequently used for partial and full dentures are represented by acrylic resins, offering to those prosthetic constructions sufficient strength and a proper aesthetic appearance. The question that arises related to the practical aspects is whether conventional technologies remain the method of choice for getting full dentures and whether digital technologies can be implemented to obtain these prosthetic constructions. In recent years, CAD / CAM technologies for complete dentures realization became better known and more available, working flow and materials becoming more efficient, allowing to gain prosthetic constructions that satisfy the highest functional requirements. These procedures offer significant benefits to the dentist, dental technician and also to the patients. The present study analyzes the opinion of dental technicians regarding these modern methods of getting mobile prostheses and notice the percent of use of the digital technologies into the dental laboratories.